Implementasi Peraturan Menteri dalam Negeri Nomor 59 Tahun 2021 Tentang Penerapan Standar Pelayanan Minimal (Studi pada penilaian SPM Di Sekretariat Kota Metro) - Nur Afni Agustin; Nyimas Lidya putri pertiwi; Saipullah; Taufid Hidayat Nazar (CV. Creative Tugu Pena, 2024)
This study aims to identify the obstacles faced by the SPM Preparation Team at the Metro City Regional Secretariat, in filling in the SPM indicator achievements and finding solutions to overcome these problems. The research method used is descriptive qualitative, with data obtained through interviews, observation and documentation studies. The results of this research show that Minister of Home Affairs Regulation Number 59 of 2021 concerning the Implementation of Minimum Service Standards. Minimum Service Standards, hereinafter abbreviated to SPM, are provisions regarding the type and quality of basic services which constitute Mandatory Government Affairs which every citizen has the right to obtain at a minimum. The types of services and indicators used as measures and achievement targets are determined by the Government through the relevant sectors. One of the objectives of regulating this SPM is to guarantee basic services which are the rights of every resident of the Metro city area which must be fulfilled by the Government. Even though they succeeded in getting the title of the best SPM in the City category in Indonesia, in practice there are a number of problems that are often faced by the SPM Preparation Team at the Metro City Regional Secretariat, in their efforts to achieve minimum service standard indicators. Some of the main obstacles in the implementation of SPM in Metro Cities include incomplete achievement of filling in indicators, inadequate quality of human resources (HR), as well as mismatches in the budget allocated for SPM. In addition, there is often a change in human resources which has a negative impact on the preparation of SPM indicator achieve.